QoS Optimization and Bufferbloat Mitigation in 5G Standalone Networks using 5QI Mapping - Ghina Rezkiah Octavia; Sopian Soim; Eka Susanti (Universitas Islam Indragiri, 2026)
Bufferbloat in the Best Effort traffic profile (5QI = 9) of open-source 5G Standalone (5G SA) networks leads to excessive packet queuing at the User Plane Function (UPF) and gNodeB, resulting in significant degradation of 4K video streaming performance under network congestion. This study investigates the effectiveness of 5QI = 4 mapping for mitigating bufferbloat and optimizing the Quality of Service (QoS) of 4K video streaming in 5G SA networks using secondary data compiled from previous studies. A quantitative comparative analysis was conducted using QoS metrics, including throughput, delay, jitter, and packet loss, systematically extracted from 30 peer-reviewed publications published between 2021 and 2026 following the PRISMA protocol. The results demonstrate that mapping traffic to the 5QI = 4 priority class consistently maintains 4K video throughput above the critical threshold of 25 Mbps across different experimental platforms, reduces end-to-end latency to below 150 ms in accordance with the ITU-T Y.1541 Class 4 recommendation, and limits jitter to less than 15 ms. The proposed mapping strategy prioritizes packet scheduling at the UPF through the N4 interface under the control of the Session Management Function (SMF), while intentionally deprioritizing and, when necessary, dropping lower-priority background traffic to preserve service quality for delay-sensitive applications. Furthermore, the findings demonstrate that modifying the MongoDB policy database within the Policy Control Function (PCF) of Open5GS is an effective approach for mitigating network congestion and eliminating visual stuttering during Ultra High Definition (UHD) video streaming.